Indirect Enzyme Linked Immunosorbent Assay Sebagai Metode untuk Melacak Bruselosis pada Sapi Perah (INDIRECT ENZYME IMMUNOSORBENT ASSAY (I-ELISA) AS METHOD FOR DETECT BRUCELLOSIS IN DAIRY COW) - Ghurafa, Rinaldi; Lukman, Denny Widaya; Latif, Hadri (Jurnal Veteriner; Vol 20 No 1 (2019)DO - 10.19087/jveteriner.2019.20.1.30, 2019)
Brucellosis has become a zoonotic disease that received attention in efforts to prevent and eradicate strategic infectious animal diseases in Indonesia. Brucellosis can be detected early by the rose bengal test (RBT), followed by complement fixation test (CFT) and by enzyme linked immunosorbent assay (ELISA). The aims of this research was to study the indirect enzyme linked immunosorbent assay test (I-ELISA) as an alternative test for detecting brucellosis in dairy cattle. The method was used by conducting tests of RBT, CFT, I-ELISA and commercial I-ELISA to test brucellosis. The test results were calculated sensitivity and specificity, as well as analyzed by calculating the kappa value. The method was used by conducting tests of RBT, CFT, I-ELISA and commercial I-ELISA to test brucellosis. The test results were calculated for sensitivity and specificity, as well as analyzed by calculating the Kappa statistical value. The results of the sensitivity and specificity calculation showed that the indirect enzyme linked immunosorbent assay (I-ELISA) test developed a higher sensitivity (100%) compared to RBT test (93.75%) and commercial I-ELISA (93.75%). The developed I-ELISA specificity (74.68%) was still lower than RBT (89.87%), but higher than commercial I-ELISA (70.52%). The calculation of the statistical value of kappa RBT with CFT showed the kappa value 0.7120 which meaned it had a good agreement, commercial I-ELISA with CFT showed kappa value 0.6165 which meaned it had good suitability, whereas I-ELISA developed with CFT showed kappa value 0.4984 which meaned having a moderate agreement.In conclusion, the indirect enzyme linked immunosorbent assay (I-ELISA) which had been developed had low specificity, but the sensitivity was the highest compared to the commercial I-ELISA test and RBT, so this test was appropriate to be used as a screening test, especially in dairy cows movement into brucellosis-free areas or regions.